Perlakuan Akuntansi Terhadap Piutang Pada Unit Bisnis Infrastruktur PT PLN Batam - Shinta Wahyu Hati; Yulia Nababan (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2014)
Research was conducted in Service of National Electricity Company Batam .The purpose of this research is to find treatment on corporate accounting business units in infrastructure pt pln batam whether it had in accordance with the principle of accounting. This study using a method of analysis of data descriptive, and this research result indicates that accounting treatment on corporate business units in infrastructure pt pln batam includes recognition of receivable , the registration of receivable , the assessment of receivable, presentation of corporate debt and not in accordance with pabu. The results of research shows that the first, recognition of receivable done business units infrastructure Service of National Electricity Company Batam not in accordance with the principle generally accepted accounting, a unit of business infrastructure pt pln batam admit only the use of electric pole at the time of the course. The second, recording on corporate accounting business units in infrastructure Service of National Electricity Company Batam not in accordance with the principle of public accounting grateful. Thirdly, Infrastructure Business Unit PT PLN has not made the recording in the form of a journal which is needed in recognition, assessment and record keeping